Performance-Based Management for Organizational Productivity Enhancement: A Systematic Review - Andi Ibbar; A Muhammad Fadli Mappisabbi (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
Performance-based management (PBM) has emerged as a critical strategic approach for enhancing organizational productivity in contemporary business environments. This systematic review examines the theoretical frameworks, implementation strategies, and empirical evidence regarding PBM systems and their impact on organizational performance from 2020 to 2025. Through analysis of peer-reviewed literature, this article identifies key mechanisms through which performance management systems influence productivity outcomes, explores organizational challenges in implementation, and proposes evidence-based recommendations for practitioners. The findings suggest that effectively designed and implemented PBM systems, when aligned with organisational strategy, employee development, and stakeholder engagement, significantly contribute to improved productivity metrics. However, success depends on comprehensive change management, adequate resource allocation, and continuous system refinement. This review provides both theoretical insights and practical guidance for organizations seeking to optimize their performance management approaches.